2007
DOI: 10.1523/jneurosci.5066-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Increases A1Adenosine Receptor Binding in the Human Brain: A Positron Emission Tomography Study

Abstract: It is currently hypothesized that adenosine is involved in the induction of sleep after prolonged wakefulness. This effect is partially reversed by the application of caffeine, which is a nonselective blocker of adenosine receptors. Here, we report that the most abundant and highly concentrated A 1 subtype of cerebral adenosine receptors is upregulated after 24 h of sleep deprivation. We used the highly selective A 1 adenosine receptor (A 1 AR) radioligand [ In sleep deprived subjects, we found an increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
112
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(127 citation statements)
references
References 29 publications
9
112
1
2
Order By: Relevance
“…This fluctuation in adenosine over the sleep-wake cycle has also been observed in the forebrain of animals (Porkka-Heiskanen 1997). Studies have observed both this natural homeostatic oscillation of adenosine as well as an increase in adenosine signaling with extended periods of wakefulness (Porkka-Heiskanen 1997;Basheer et al 2007;Elmenhorst et al 2007). The increase in adenosine after periods of wakefulness contributes to the increased drive for sleep.…”
Section: Adenosine and Astrocytesmentioning
confidence: 63%
“…This fluctuation in adenosine over the sleep-wake cycle has also been observed in the forebrain of animals (Porkka-Heiskanen 1997). Studies have observed both this natural homeostatic oscillation of adenosine as well as an increase in adenosine signaling with extended periods of wakefulness (Porkka-Heiskanen 1997;Basheer et al 2007;Elmenhorst et al 2007). The increase in adenosine after periods of wakefulness contributes to the increased drive for sleep.…”
Section: Adenosine and Astrocytesmentioning
confidence: 63%
“…As shown previously, there is a high test-retest reliability of A 1 AR availability after an 8-h sleep episode (29), which is also comparable between groups of the same age (30). Receptor binding data of earlier experiments after 8 h of sleep at night (27,29) were therefore integrated into the present analyses as independent control group values (Table 1).…”
mentioning
confidence: 81%
“…However, positron emission tomography (PET) is a tool that allows for exploring adenosine receptors in vivo. In earlier experiments, we already found evidence that A 1 AR availability is stable after repeated 8-h sleep episodes (29) and increased after 24 h of sleep deprivation (27). In the present study, we intended to increase sleep pressure even further to examine if A 1 AR availability is satiating, as predicted by the two-process model, and whether the exponential discharge of sleep pressure during recovery sleep is reflected in A 1 AR availability.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Adenosine receptors have been implicated in regulating coronary blood flow and oxygen consumption by cardiac muscle and are present in the brain, most notably in the forebrain [34,35]. CBD (50 μg/kg) inhibits the subsequent ventricular tachycardia following coronary artery occlusion in rats-an effect abolished by 8-cyclopentyl-1,3-dipropylxanthine, an adenosine A 1 receptor antagonist (Table 1).…”
Section: Adenosinementioning
confidence: 99%